Twelve-crystal prototype of Li2MoO4 scintillating bolometers for CUPID and CROSS experiments - Alfonso, K.; Armatol, A.; Augier, C.; Avignone III, F. T.; Azzolini, O.; Balata, M.; Bandac, I.C.; Barabash, A. S.; Bari, G.; Barresi, A.; Baudin, D.; Bellini, F.; et al. (Journal of Instrumentation, 2024)
An array of twelve 0.28 kg lithium molybdate (LMO) low-temperature bolometers equipped with 16 bolometric Ge light detectors, aiming at optimization of detector structure for CROSS and CUPID double-beta decay experiments, was constructed and tested in a low-background pulse-tube-based cryostat at the Canfranc underground laboratory in Spain. Performance of the scintillating bolometers was studied depending on the size of phonon NTD-Ge sensors glued to both LMO and Ge absorbers, shape of the Ge light detectors (circular vs. square, from two suppliers), in different light collection conditions (with and without reflector, with aluminum coated LMO crystal surface). The scintillating bolometer array was operated over 8 months in the low-background conditions that allowed to probe a very low, μBq/kg, level of the LMO crystals radioactive contamination by 228Th and 226Ra.
Keywords: Li2MoO4; CUPID experiments; CROSS experiments